EVALUASI KEBIJAKAN PEMANFAATAN RUANG KAWASAN PESISIR DAN KEPULAUAN DI KOTA TERNATE PROVINSI MALUKU UTARA - Isran Abdul Syukur; Sri Suwitri (Departemen Administrasi Publik, Universitas Diponegoro, 2018)
The utilization of coastal spatial in Ternate is always increasing, which one of the coastal in downtown Ternate especially in Ternate Tengah and its arround becoming a pledge of Ternate’s government in order to be service, trade, port and tourism center according to spatial planning and territory 2012-2032 with main purpose for increasing PAD (Pendapatan Anggaran Daerah) sources. The rapid development of coastal spatial utilization in Ternate without considering the coastal ecological aspects is worried to impact spreadly the abrasion in around coastal. The raising of economy and society activities in this coastal spatial become a necessity that can not be avoid as the center of Ternate’s society basic needs. However, the development of coastal spatial utilization has been shifted by the Ternate’s vision and mission that is BAHARI BERKESAN “Berbudaya, Agamais, Harmonis, Mandiri, Berkeadilan dan Berwawasan Lingkungan”. This vision is materialized in the Ternate’s development mission 2011-2015 with the purpose of spatial planning that is “Mewujudkan Kota Ternate sebagai Kota Pesisir dan Kepulauan yang adil, Mandiri dan Berkelanjutan berbasis pada sektor unggulan jasa perdagangan, perikanan dan periwisata”. The result of this research showed policy commitment is required on the Ternate’s vision and mission to build Ternate as a town with coastal environment perspective and equitable, autonomous, sustainable archipelago had been ignored which coastal spatial and archipelago is not as a friendly spatial to the environment and society anymore.